Asymptomatic female softball pitchers have altered hip morphology and cartilage composition - Stuart J. Warden; Sally L. Coburn; Robyn K. Fuchs; Rachel K. Surowiec; Julio Carballido-Gamio; Joanne L. Kemp; Peter K. Jalaie; David F. Hanff; Antony J. R. Palmer; Scott J. Fernquest; Kay M. Crossley; Joshua J. Heerey (Scientific Reports)
Abstract Few studies have explored hip morphology and cartilage composition in female athletes or the impact of asymmetric repetitive loading, such as occurs during softball pitching. The current cross-sectional study assessed bilateral bony hip morphology on computed tomography imaging in collegiate-level softball pitchers (‘Pitch1’, n = 25) and cross-country runners (‘Run’, n = 13). Magnetic resonance imaging was used to assess cartilage relaxation times in a second cohort of pitchers (‘Pitch2’, n = 10) and non-athletic controls (‘Con’, n = 4). Pitch1 had 52% greater maximum alpha angle than Run (p < 0.001) and were 21.3 (95% CI 2.4 to 192.0) times more likely to have an alpha angle ≥ 60° within at least one hip. Pitch2 had longer T2 relaxation times in the superior femoral cartilage of the drive leg (same side as the throwing arm) and stride leg than Con (all p < 0.02). The drive leg in Pitch2 had longer T1ρ and T2 relaxation times in the superior femoral cartilage compared to the stride leg (all p ≤ 0.03). Asymptomatic softball pitchers exhibit altered bony hip morphology and cartilage composition compared to cross-country runners and non-athletic controls, respectively. They also exhibit asymmetry in cartilage composition. Further studies with larger sample sizes are warranted and any potential long-term consequences of the changes in terms of symptom and osteoarthritis development requires investigation.